The Impact of Classical Greece on European and National Identities - Haagsma, M., (Publications of the Netherlands Institute at Athens ;, 2003)
These thirteen papers, from a colloquium held at the Netherlands Institute at Athens in 2000, examine European scholarship's fascination with classical Greece during the 19th and 20th centuries. Arranged geographically and then thematically, the papers discuss Greek attitudes towards classical archaeology and literature, Germany and Neoclassicism, classical Greece in Dutch literature and the influence of Greece on Dutch politics, the influence of Alexander the Great and the Persian Wars, the classical element in Victorian verse and interpretations of Homeric epic.